The anti-inflammatory effects of photobiomodulation are mediated by cytokines: Evidence from a mouse model of inflammation - Shamloo, Shirin; Defensor, Erwin; Ciari, Peter; Ogawa, Gaku; Vidano, Laura; Lin, Jennifer S.; Fortkort, John A.; Shamloo, Mehrdad; Barron, Annelise E. (Frontiers in Neuroscience, 2023)
There is an urgent need for therapeutic approaches that can prevent or limit neuroinflammatory processes and prevent neuronal degeneration. Photobiomodulation (PBM), the therapeutic use of specific wavelengths of light, is a safe approach shown to have anti-inflammatory effects. The current study was aimed at evaluating the effects of PBM on LPS-induced peripheral and central inflammation in mice to assess its potential as an anti-inflammatory treatment. Daily, 30-minute treatment of mice with red/NIR light (RL) or RL with a 40 Hz gamma frequency flicker for 10 days prior to LPS challenge showed anti-inflammatory effects in the brain and systemically. PBM downregulated LPS induction of key proinflammatory cytokines associated with inflammasome activation, IL-1b and IL-18, and upregulated the anti-inflammatory cytokine, IL-10. RL provided robust anti-inflammatory effects, and the addition of gamma flicker potentiated these effects. Overall, these results demonstrate the potential of PBM as an anti-inflammatory treatment that acts through cytokine expression modulation.